Comparison of two adhesive systems of various polyetheretherketone (PEEK) composites on the shear bond strength - Demırcı, Fatıh; Tekin, Samet (My University, 2021)
Aim: In this in vitro study, the effect of two adhesive systems applied to surfaces of different polyether-ether-ketone (PEEK) composites on the shear bond strength (SBS) of a composite resin was compared. Methodology: Eighty PEEK specimens were divided into four groups (n=20): Unfilled PEEK (UF), carbon-fiber-reinforced PEEK (CFR), glassfiber-reinforced PEEK (GFR), and ceramic-reinforced PEEK (CR). Each group was further divided into two subgroups (n=10): Visio.link (VL) and Single Bond Universal (SB). The specimens with 8-mm diameter and 5-mm thickness were prepared. SBS was examined using a universal testing machine. Results were statistically analyzed by multivariate analysis of variance and Tukey’s post-hoc test. Failure modes were analyzed using a stereomicroscope at 20× magnification. Surface properties were examined by scanning electron microscopy. The surface properties of the specimens were examined by scanning electron microscopy (SEM). Results: Effect of different PEEK and adhesive systems on SBS was found to be statistically significant (p<0.05). SBS values for CFR-VL and UF-VL groups were statistically more significant than those for CFR-SB and UF-SB groups. SBS values for the GFR-VL group were statistically more significant than that for the UF-VL group. SBS values for the CF-SB group were statistically more significant than those for CFR-SB and CFR-SB groups. Failure modes were examined using a stereomicroscope at 20× magnification, and adhesive and mixed failure modes were observed. Conclusion: PEEK composites with different contents and properties can be used in fixed prosthetic restorations. However, additional experimental and clinical studies are required to investigate different PEEK frameworks and composite veneers.
Keywords: Diş Hekimliği